Phenotypic integration in the carnivoran backbone and the evolution of functional differentiation in metameric structures. Issue 3 (10th April 2021) - Martín‐Serra, Alberto; Pérez‐Ramos, Alejandro; Pastor, Francisco J.; Velasco, David; Figueirido, Borja
Abstract: Explaining the origin and evolution of a vertebral column with anatomically distinct regions that characterizes the tetrapod body plan provides understanding of how metameric structures become repeated and how they acquire the ability to perform different functions. However, despite many decades of inquiry, the advantages and costs of vertebral column regionalization in anatomically distinct blocks, their functional specialization, and how they channel new evolutionary outcomes are poorly understood. Here, we investigate morphological integration (and how this integration is structured [modularity]) between all the presacral vertebrae of mammalian carnivorans to provide a better understanding of how regionalization in metameric structures evolves. Our results demonstrate that the subunits of the presacral column are highly integrated. However, underlying to this general pattern, three sets of vertebrae are recognized as presacral modules—the cervical module, the anterodorsal module, and the posterodorsal module—as well as one weakly integrated vertebra (diaphragmatic) that forms a transition between both dorsal modules. We hypothesize that the strength of integration organizing the axial system into modules may be associated with motion capability. The highly integrated anterior dorsal module coincides with a region with motion constraints to avoid compromising ventilation, whereas for the posterior dorsal region motion constraints avoid exceeding extension of the posterior back. On the other hand, the weakly integrated diaphragmatic vertebra belongs to the "Diaphragmatic joint complex"—a key region of the mammalian column of exceedingly permissive motion. Our results also demonstrate that these modules do not match with the traditional morphological regions, and we propose natural selection as the main factor shaping this pattern to stabilize some regions and to allow coordinate movements in others.